Aplikasi Analytical Hierarchy Process: Sistem Pendukung Keputusan untuk Seleksi Desa Inovasi di Wilayah Sorong - Ismail, Ismail; Ulat, Muhamad Ali; Muhfizar, Muhfizar; Mustasim, Mustasim; Poltak, Hendra (Jurnal Ilmu Pertanian Indonesia, 2021)
Rural-urban social inequality is a problem that must be solved to achieve prosperity and economic justice that is desired by all human beings. Efforts to overcome the problem are to create and carry out the Program of Marine and Fisheries Innovation Village which is a program of marine and fisheries community empowerment to be able to take advantage of technology and innovation as an effort to improve their lives. Limited budget and resources cause not all villages that are partners in community service at the Sorong Marine and Fisheries Polytechnic can be turned into Marine and Fisheries Innovation Villages. This research was conducted to determine the priority ranking of villages to be selected and to carry out innovation and technology interventions according to the predetermined criteria. Decision making in this marine and fisheries innovation village requires a systematic and accurate method using the Analytical Hierarchy Process (AHP). In the case study, the selection of the innovation village program was carried out at three locations in the Sorong area (Walal Village, Rimbapala Village, and Pulau Raam Village). The criteria used in the selection of alternative innovation villages were: 1) having local government support, 2) community response, 3) having superior fishery commodities, 4) accessibility, and 5) in accordance with the resources owned by the KP Sorong Polytechnic. The results obtained based on the AHP method were Raam Island 58,7%, Walal 21,9%, and Rimbapala 19,4%. The conclusion is that the village selected as the innovation village is Raam Island with the highest score of 58,7%. Keywords: alternatives, analytical hierarchy process, criteria, innovation village, options